2021
DOI: 10.1016/j.ultsonch.2021.105548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preliminary treatment by ultrasonic and convective air drying on the properties and oil absorption of potato chips

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…In addition, the chips had more pores and cracks. The hardness of chips also increased with increasing frying time [ 69 ].…”
Section: Application Of Ultrasound Methodsmentioning
confidence: 99%
“…In addition, the chips had more pores and cracks. The hardness of chips also increased with increasing frying time [ 69 ].…”
Section: Application Of Ultrasound Methodsmentioning
confidence: 99%
“…Several studies have confirmed that ultrasound pretreatment of fruit (e.g., genipap, apple, strawberries, orange peel) can increase the water diffusivity, leading to a reduction in the total drying time 18‐22 . The increased water diffusivity of fruit can occur due to the formation of micropores on the surface of fruit during ultrasound pretreatment 23 . On the other hand, ascorbic acid is a hypertonic solution that is normally used as an anti‐darkening agent during fruit dehydration.…”
Section: Introductionmentioning
confidence: 98%
“…[18][19][20][21][22] The increased water diffusivity of fruit can occur due to the formation of micropores on the surface of fruit during ultrasound pretreatment. 23 On the other hand, ascorbic acid is a hypertonic solution that is normally used as an anti-darkening agent during fruit dehydration. It has been reported that the pretreatment of fruit with ascorbic acid can slow oxidation reactions and prevent browning during drying.…”
Section: Introductionmentioning
confidence: 99%
“…This process results in physical and chemical alterations to the tissues and internal components of the cells, promoting a crispy crust formation and developing a delicious product [ 1 , 2 ]. Due to their unique sensory properties, potato chips have become the most popular snack for ordinary customers [ 3 ]. However, the excessive oil content concerns consumers, driving up searches for alternatives to produce oil-free potato chips or potato chips with reduced oil concentration [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique sensory properties, potato chips have become the most popular snack for ordinary customers [ 3 ]. However, the excessive oil content concerns consumers, driving up searches for alternatives to produce oil-free potato chips or potato chips with reduced oil concentration [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%